2023
DOI: 10.3390/ijerph20054358
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation as a Therapeutic Exercise Tool versus Face-to-Face Physiotherapy: A Systematic Review

Abstract: Digital physiotherapy, often referred to as “Telerehabilitation”, consists of applying rehabilitation using telecommunication technologies. The objective is to evaluate the effectiveness of therapeutic exercise when it is telematically prescribed. Methods: We searched PubMed, Embase, Scopus, SportDiscus and PEDro (30 December 2022). The results were obtained by entering a combination of MeSH or Emtree terms with keywords related to telerehabilitation and exercise therapy. RCTs on patients over 18 years and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Telerehabilitation has been shown to achieve high levels of patient satisfaction and adherence, with values like those of traditional face-to-face/in-person rehabilitation methods. This suggests that telerehabilitation can be a viable and effective alternative for delivering rehabilitation interventions, with outcomes to comparable those of conventional in-person physiotherapy [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telerehabilitation has been shown to achieve high levels of patient satisfaction and adherence, with values like those of traditional face-to-face/in-person rehabilitation methods. This suggests that telerehabilitation can be a viable and effective alternative for delivering rehabilitation interventions, with outcomes to comparable those of conventional in-person physiotherapy [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data analytics can further fine-tune treatment plans and provide valuable insights for ongoing research. Overall, the adoption of telehealth and app-based solutions in post-ICU rehabilitation has the potential to overcome current barriers associated with ICU follow-up services and improve both functional outcomes and QOL for survivors of critical illness [ 157 , 158 ].…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…According to recent research, telehealth physical therapy is cost-effective ( Cottrell et al, 2017 ; Nelson et al, 2021 ), and studies have shown promising outcomes in the treatment of pulmonary and heart disease ( Tsai et al, 2017 ), arthritis and musculoskeletal conditions ( Cottrell et al, 2017 ), post-operative rehabilitation ( Pastora-Bernal et al, 2017 ), and breast cancer ( Galiano-Castillo et al, 2016 ). Other studies found that telehealth physical therapy improves patients' adherence to treatment and reduces health costs ( Bettger et al, 2020 ; Muñoz-Tomás et al, 2023 ). These studies have provided evidence of the effectiveness of telehealth physical therapy but suffered from many methodological weaknesses ( Turolla et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%